CRM197 reverses paclitaxel resistance by inhibiting the NAC‐1/Gadd45 pathway in paclitaxel‐resistant ovarian cancer cells. (6th September 2019) - Tang, Xiao‐han; Li, Hui; Zheng, Xiu‐shuang; Lu, Mei‐song; An, Yuan; Zhang, Xiao‐lei
Abstract: Heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF) is a new promising target for the treatment of ovarian cancer. Our previous study showed that cross‐reacting material 197 (CRM197), a specific HB‐EGF inhibitor, significantly reverses resistance against paclitaxel in paclitaxel‐resistant ovarian cancer cells. However, the mechanism of the effect of CRM197 on the reversion of paclitaxel resistance was unclear. In this study, in vitro and in vivo data suggested that CRM197 treatment sensitized paclitaxel‐resistant ovarian cancer cells to paclitaxel, at least in part, via nucleus accumbens‐1 (NAC‐1) and its downstream pathway, DNA damage‐inducible 45‐γ interacting protein (Gadd45gip1)/growth arrest and DNA damage‐inducible 45 (Gadd45), in A2780/Taxol and SKOV3/Taxol cells. The results also showed that CRM197 activated the proapoptotic JNK/p38MAPK pathway to enhance caspase‐3 activity and apoptosis by downregulation of the NAC‐1/Gadd45gip1/Gadd45 pathway, leading to reversion of paclitaxel resistance in A2780/Taxol and SKOV3/Taxol cells. This study provides the first mechanism through which CRM197 significantly reverses resistance against paclitaxel by modulating the NAC‐1/Gadd45gip1/Gadd45 pathway in paclitaxel‐resistant ovarian cancer cells, and the mechanism of HB‐EGF inhibition as a novel therapeutic strategy for patients with paclitaxel‐resistant ovarian cancer. Abstract : CRM197 treatment sensitized the paclitaxel‐resistant ovarian cancer to paclitaxel, at least in part, via NAC‐1 and its downstream Gadd45gip1/ Gadd45 pathway in A2780/Taxol and SKOV3/Taxol cells. The data also shown that CRM197 activates the proapoptotic JNK/p38MAPK pathway to enhance caspase‐3 activity and cell apoptosis by the downregulation of NAC‐1/Gadd45gip1/Gadd45 pathway, resulting in the reversion of paclitaxel resistance in A2780/Taxol and SKOV3/Taxol cells. This study provides the first mechanism through which CRM197 significantly reverses resistance against paclitaxel by modulating the NAC‐1/Gadd45gip1/Gadd45 pathway in paclitaxel‐resistant ovarian cancer cells, and the mechanism of HB‐EGF inhibition as a novel therapeutic strategy for patients with paclitaxel‐resistant ovarian cancer.